Analisis Bibiometrik Untuk Menganalisis Keterkaitan Psikologi Dalam Pariwisata - Kiki Rizki Makiya; Hendi Prasetyo; Amin Kiswantoro; Fitria Noviati (Jayapangus Press, 2023)
The relevance of the field of psychology in the tourism sector has become the focus of research by researchers. This study aims to analyze the development of psychology research in the field of tourism using a bibliometric approach. The data used are articles published from various sources from 2018 to 2022 with the theme of tourism psychology. Data collection and analysis were carried out using the Publish or Perish (PoP) application with the Google Scholar database. The research data was analyzed using the VoS Viewer application. The results of the analysis show that in the 2018–2022 period, there were 441 published articles regarding the interrelationship of psychology and tourism. The total citations for these articles reached 1649. The most cited articles were those written by Jiang, et al. in 2019, with a total of 200 citations. Data mapping based on co-word analysis revealed that there were 12 clusters that formed research groups with interrelated topics. In addition, the grouping based on co-author analysis shows that there are four clusters that reflect the collaboration between authors in this research field. Thus, this study provides an overview of the development of psychology research in the field of tourism using bibliometric analysis. From several existing research topics, future research can be carried out, such as the topic of tourism psychology related to social media, tourism psychology related to the content, psychologically what underlies people's desire to travel religiously, and topics related to innovation in tourism psychology. This information can be the basis for understanding research trends, collaborations between researchers, and research topics that are most relevant in relation to the psychology of tourism.